Geometallurgy and the future of digital mining in Peru - Torres Guerra, Jesús Alberto (2021)
Today, we are facing the fourth industrial revolution, which involves the emergence of new technologies such as robotics, machine learning systems, artificial intelligence, high-performance networks, and multi-cloud, among others. These developments, such as machine learning (machine learning), present themselves as an opportunity for the mining industry. In particular, for the field of Geometallurgy, which requires the integration of predictive models throughout the mining value chain (Geometallurgical Model). This scenario provides an innovative approach to significantly impact decision-making, leading to improved planning and optimization of processes. This article addresses the state of the art of Geometalurgia in the digital age, and presents the technological advances used in the mining industries. Likewise, the current situation of Geometalurgia in the Peruvian mines is presented.